THE EFFECT OF A THEORY OF REASONED ACTION ON INTENTIONAL BEHAVIOR AND ITS IMPACT ON BEHAVIOR IN PURCHASING HALAL IMPORTED PRODUCTS - Najmudin, Najmudin; Syihabudin, Syihabudin; Saleh, Suja'i; Ma'zumi, Ma'zumi; ikmalia, Nuha; Salsabila, Nufaila (Proceedings of the International Conference of Islamic Economics and Business (ICONIES), 2024)
This study aims to determine (1) the effect of subjective norms on intentional behavior in purchasing halal imported products (2) the effect of attitudes on intentional behavior in purchasing halal imported products (3) the effect of subjective norms on behavior in purchasing halal imported products, (4) the effect of attitudes on intentional behavior in purchasing imported products (5) the effect of intentional behavior in purchasing halal imported products, (6) the effect of subjective norms on behavior in purchasing halal imported products through intentional behavior, ( 7) the effect of attitudes on behavior in purchasing halal imported products through intentional behavior. The method used in this research is quantitative, with the population of Banten Province millennial society who have purchased halal imported products, the sampling technique uses purposive sampling, and the data collection technique uses a questionnaire. The data was processed using Smart PLS 3.2.9 software and analyzed using the structural equation modeling (SEM) method with a partial least squares (PLS) approach. The results of this study indicate that (1) subjective norms have a significant positive effect on intentional behavior in purchasing halal imported products (2) attitudes have a significant positive effect on intentional behavior in purchasing halal imported products (3) subjective norms have a positive and insignificant effect on behavior in purchasing halal imported products, (4) attitudes have a significant positive effect on intentional behavior in purchasing imported products (5) intentional behavior has a significant positive effect on behavior in purchasing halal imported products, (6) subjective norms through intentional behavior have a significant positive effect on behavior in purchasing halal imported products, (7) attitudes through intentional behavior have a significant positive effect on behavior in purchasing halal imported products.